2021
DOI: 10.1002/elan.202100077
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of Acid Pretreated 3D‐printing Composite for the Heavy Metal Ions Analysis

Abstract: The performance enhancement of 3D‐printed electrode comprised of polylactic acid (PLA) and graphite (Gr) doped with graphene oxide (GO) was studied to detect five heavy metal ions in trace level. The pretreatment of PLA/Gr/GO electrode with potential cycling in H2SO4 solution achieved the most sensitive response. The characteristics of the composite electrodes were verified using XPS, FE‐SEM, EDXS, Raman, and impedance spectroscopy. The experimental variables affecting the response current were optimized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thus, two approaches are mostly explored aiming to enhance the conductivity of the 3D-based sensors: (i) the use of surface treatments (an issue addressed in section 5) and (ii) the use of lab-made manufactured filaments with a higher percentage of conductive material. The second approach explores to load the polymer thermoplastic with conductive materials, such as graphite, 17,36−38 graphene, 21,39,40 carbon black, 19 carbon nanotubes, 41 and metallic nanoparticles, 20,42 being possible to combine one or more of the aforementioned conductive materials 21,43 lab-made filaments are the most important parameters evaluated to check the proportion of conductive material inserted in the structure of the thermoplastic polymer. For instance, Foster and colleagues 17 reported an interesting way to manufacture a nanographite-based homemade filament (NG/PLA) aiming the production of improved sensors for the simultaneous detection of lead(II) and cadmium(II).…”
Section: D Printing In Electroanalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, two approaches are mostly explored aiming to enhance the conductivity of the 3D-based sensors: (i) the use of surface treatments (an issue addressed in section 5) and (ii) the use of lab-made manufactured filaments with a higher percentage of conductive material. The second approach explores to load the polymer thermoplastic with conductive materials, such as graphite, 17,36−38 graphene, 21,39,40 carbon black, 19 carbon nanotubes, 41 and metallic nanoparticles, 20,42 being possible to combine one or more of the aforementioned conductive materials 21,43 lab-made filaments are the most important parameters evaluated to check the proportion of conductive material inserted in the structure of the thermoplastic polymer. For instance, Foster and colleagues 17 reported an interesting way to manufacture a nanographite-based homemade filament (NG/PLA) aiming the production of improved sensors for the simultaneous detection of lead(II) and cadmium(II).…”
Section: D Printing In Electroanalysismentioning
confidence: 99%
“…Thus, two approaches are mostly explored aiming to enhance the conductivity of the 3D-based sensors: (i) the use of surface treatments (an issue addressed in section ) and (ii) the use of lab-made manufactured filaments with a higher percentage of conductive material. The second approach explores to load the polymer thermoplastic with conductive materials, such as graphite, , graphene, ,, carbon black, carbon nanotubes, and metallic nanoparticles, , being possible to combine one or more of the aforementioned conductive materials , leading to the production of the composite. The printability and the electrochemical performance of the sensors obtained by such lab-made filaments are the most important parameters evaluated to check the proportion of conductive material inserted in the structure of the thermoplastic polymer.…”
Section: D Printing In Electroanalysismentioning
confidence: 99%
“…Shin and collaborators 59 proposed a new procedure for the enhancement of 3D‐printed electrodes produced from a homemade PLA‐, graphite‐, and graphene oxide‐based filament. According to the authors, the most sensitive response for metal ions was observed after 20 cycles (from –2.0 V to +2.0 V) in 0.5 mol L −1 H 2 SO 4 solution.…”
Section: Enhancing the Electrochemical Performance Of Fdm‐based Devicesmentioning
confidence: 99%
“…Another widely explored procedure to surface posttreatment of 3D‐printed electrodes is the use of electrochemical procedures 17,22,39,55–59 . Dos Santos et al 39 .…”
Section: Enhancing the Electrochemical Performance Of Fdm‐based Devicesmentioning
confidence: 99%